2016
DOI: 10.1038/nchembio.2147
|View full text |Cite
|
Sign up to set email alerts
|

An histidine covalent receptor and butenolide complex mediates strigolactone perception

Abstract: Strigolactone plant hormones control plant architecture and are key players in both symbiotic and parasitic interactions. They contain an ABC tricyclic lactone connected to a butenolide group, the D-ring. The DWARF14 (D14) strigolactone receptor belongs to the superfamily of α/β-hydrolases and is known to hydrolyze the bond between the ABC lactone and the D-ring. Here we characterize the binding and catalytic functions of RAMOSUS3 (RMS3), the pea (Pisum sativum) ortholog of rice (Oryza sativa) D14 strigolacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
357
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(376 citation statements)
references
References 50 publications
19
357
0
Order By: Relevance
“…The activities of SLs depend on D3 and D14: D3 encodes the F-box protein and D14 encodes SL receptor, which act in SL signaling. D53, which encodes a substrate of the SCF D3 complex, was recently reported to be a repressor of SL signaling in rice, and the degradation of D53 protein by SL, in cooperation with D14 and D3, is considered as a key event in SL signaling (Jiang et al, 2013;Zhou et al, 2013;Yao et al, 2016;de Saint Germain et al, 2016).…”
mentioning
confidence: 99%
“…The activities of SLs depend on D3 and D14: D3 encodes the F-box protein and D14 encodes SL receptor, which act in SL signaling. D53, which encodes a substrate of the SCF D3 complex, was recently reported to be a repressor of SL signaling in rice, and the degradation of D53 protein by SL, in cooperation with D14 and D3, is considered as a key event in SL signaling (Jiang et al, 2013;Zhou et al, 2013;Yao et al, 2016;de Saint Germain et al, 2016).…”
mentioning
confidence: 99%
“…As described above, loss-of-function d14 mutants are consistently SL-insensitive in several species (Arite et al 2009;Waters et al 2012a;Hamiaux et al 2012;Chevalier et al 2014;de Saint Germain et al 2016). Extensive biochemistry experiments have enhanced this genetic evidence.…”
Section: Kai2 and D14 Are Both Receptor Proteins And Enzymesmentioning
confidence: 89%
“…This crucial evidence revealed that binding of strigolactone to GR24 causes the lid domain of D14 to flatten and partially collapse the ligand-binding cavity, trapping a strigolactone hydrolysis product within. At the same time, another study determined that this hydrolysis product was covalently linked to the D14 catalytic His residue (de Saint Germain et al 2016). Thus, the significance of the enzymatic activity of D14 has become clearer: substrate hydrolysis is an integral step to form a catalytic intermediate that enhances the formation of a protein complex, which in turn transduces the signal.…”
Section: Kai2 and D14 Are Both Receptor Proteins And Enzymesmentioning
confidence: 98%
See 1 more Smart Citation
“…The strigolactones and their receptors make a reappearance for this year's final signaling breakthrough, in a pair of studies nominated by the Science Signaling editors that revealed a most unusual mechanism of interaction between strigolactone and the DWARF 14 (D14) strigolactone receptor (31)(32)(33). Whereas most hormones bind reversibly and noncovalently with their cognate receptors, Yao et al (31), investigating the Arabidopsis receptor, and de Saint Germain et al (32), investigating the pea receptor, found that D14 hydrolyzes strigolactone to create its own ligand. The active ligand then binds covalently to the D14 receptor, triggering a major conformational change that enables it to trigger downstream strigolactone signaling.…”
Section: Liquid Phase Separationmentioning
confidence: 99%